Совершенствование оценки качества оказания государственных услуг - Vladimir Evgenyevich Kalugin (Вестник СибАДИ)
The problems of state services extensions are examined. It is proposed, with the aim of improving the quality and increasing the share of state services market, should be guided by the principles of quality management. To assess the quality of services is recommended to use a system of individual indicators. It allows to a comprehend sive assessment of the quality of state services in the promotion of employment on the basis of the interpretation of the vector expressed needs and actual achievements. The data on the share change of the Coverage public services non-working population and employers are given.